Factors Associated with Disaster Response Self-Efficacy among Nursing Students in Indonesia - Ferdy Lainsamputty; Priscillia M. Saluy (STIKep PPNI Jawa Barat, 2026)
Background: Disaster preparedness is a critical competency for nursing students, as they are expected to respond effectively in emergency and disaster situations. However, the level of disaster response self-efficacy (DRSE) and its associated factors among nursing students in Indonesia remain unclear. This study aimed to identify factors associated with DRSE among nursing students. Design: A cross-sectional design was used. Methods: This study involved 234 students from a university in North Sulawesi Province, Indonesia, selected through convenience sampling. Data were collected in May 2023 using the Disaster Response Self-Efficacy Scale (DRSES) and analyzed using descriptive statistics, independent t-test, Pearson correlation, and multiple linear regression. Results: The mean DRSES score was 3.31 (SD=0.66). Age was positively correlated with self-efficacy (r=0.188, p=0.004). Significant differences were also found for academic level (t=-4.974, p<0.001), disaster experience (t=-2.613, p=0.010), disaster organization involvement (t=-2.231, p=0.027), disaster training (t=-2.883, p=0.004), and disaster course participation (t=-3.320, p=0.001). Academic level emerged as the only significant determinant of DRSE (β=0.293, 95% CI [0.166 to 0.626], p<0.001). The overall model was statistically significant (p<0.001), explaining 15.6% of the variance. Conclusions: DRSE among nursing students was moderate, with academic level as the primary determinant. The findings underscore the need for curriculum enhancement through structured disaster education, simulation-based training, and experiential learning to better prepare nursing students for real-world disaster response